Toward Pediatric T Lymphoblastic Lymphoma Stratification Based on Minimal Disseminated Disease and NOTCH1/FBXW7 Status - Trinquand, Amélie; Plesa, Adriana; Abdo, Chrystelle; Subtil, Fabien; Aladjidi, Nathalie; Rigaud, Charlotte; Touzart, Aurore; Lhermitte, Ludovic; Petit, Arnaud; Michaux, Katell; Jung, Charlotte; Chassagne‐Clement, Catherine; et al. (HemaSphere, 2021)
While outcome for pediatric T lymphoblastic lymphoma (T‐LL) has improved with acute leukemia‐type therapy, survival after relapse remains rare. Few prognostic markers have been identified: NOTCH1 and/or FBXW7 (N/F) mutations identify good prognosis T‐LL and high‐level minimal disseminated disease (MDD) is reported to be of poor prognosis. We evaluated MDD and/or MRD status by 8‐color flow cytometry and/or digital droplet PCR in 82 pediatric T‐LL treated according to the EURO‐LB02 prednisone reference arm. Both techniques gave identical results for values ≥0.1%, allowing compilation. Unlike historical studies, an MDD threshold of 1% had no prognostic significance. The 54% (42/78) of patients with MDD ≥0.1% had a relatively favorable outcome (5‐y overall survival [OS] 97.6% versus 80.6%, P = 0.015, 5‐y event‐free‐survival [EFS] 95.2% versus 80.6%, P = 0.049). MDD lower than 0.1% had no impact in N/F mutated T‐LL, but identified the N/F germline patient with a high risk of relapse. Combining oncogenetic and MDD status identified 86% of patients (n = 49) with an excellent outcome and 14% of N/F germline/MDD <0.1% patients (n = 8) with poor prognosis (5y‐OS 95.9% versus 37.5%, P < 0.001; 5y‐EFS 93.9% versus 37.5%, P < 0.001). If confirmed by prospective studies, MDD and N/F mutational status would allow identification of a subset of patients who merit consideration for alternative front‐line treatment.